Endocrine activities of phthalate alternatives; assessing the safety profile of furan dicarboxylic acid esters using a panel of human cell based reporter gene assays. Issue 6 (4th March 2020) - van Vugt-Lussenburg, Barbara M. A.; van Es, Daan S.; Naderman, Matthijs; le Notre, Jerome; Klis, Frits van der; Brouwer, Abraham; van der Burg, Bart
Abstract : Ensuring non-regrettable substitution of fossil derived chemicals by biobased alternatives using human cell based reporter gene assays. Abstract : FDCA esters are highly relevant biobased alternatives for currently used benzene dicarboxylic acid esters. Despite all the developments on 2, 5-FDCA applications, to the best of our knowledge thus far no toxicological data were available for 2, 5-FDCA esters. In the present study we aimed to fill this gap, by using an in vitro reporter gene assay approach to compare the activity profile of commonly used phthalates to that of their furan-based counterparts. The assay selection was aimed at the detection of endocrine activity, since several phthalates are heavily scrutinised for their endocrine disrupting properties. However, to avoid missing other relevant toxicological endpoints, several assays able to detect various forms of cellular stress were also included in the panel. The results showed that the ( ortho )benzene dicarboxylic acid esters were predominantly active on several of the endocrine assays. In comparison, six of the seven furan dicarboxylic acid based diesters tested here showed no activity in any of the 13 assays used. Only the isobutyl derivative DIBF showed moderate estrogenic activity on one assay, compared to much more pronounced activities on four assays for the ortho -phthalate analogue. Overall, the results presented in this paper are a strong indication that 2, 5-FDCA based diesters in general are not only technically viable alternatives to phthalates, but also offer significant toxicological benefits, which supports a non-regrettable substitution.